Topographical study of O6-alkylguanine DNA alkyltransferase repair activity and N7-methylguanine levels in resected lung tissue - Crosbie, Philip A.J.; Harrison, Kathryn; Shah, Rajesh; Watson, Amanda J.; Agius, Raymond; Barber, Philip V.; Margison, Geoffrey P.; Povey, Andrew C. (Chemico-biological interactions, 2013)
•Geographical variation in susceptibility to alkylating agents in lung investigated.•MGMT repair increased towards the lung periphery.•Smoking may reduce MGMT repair in central but not peripheral lung tissue.•Alkylating agent exposure (N7-meG levels) not related to lung position.•No evidence peripheral lung more susceptible to genotoxic alkylating agents. Tobacco specific nitrosamines such as 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) are genotoxic alkylating agents found within cigarette smoke that induce lung adenocarcinomas in animal models. In humans, adenocarcinomas originate most frequently in the lung periphery. The aim of this study was to determine whether peripheral lung has increased susceptibility to the genotoxic effects of alkylating agents by comparing DNA alkylation damage (N7-methylguanine: N7-meG) and repair (O6-alkylguanine DNA alkyltransferase: MGMT) in peripheral relative to central lung tissue. Macroscopically normal lung tissue, resected from patients undergoing surgery for lung cancer, was sampled at equidistant points from central to peripheral lung along a bronchus. N7-meG levels were determined using an immunoslotblot technique and MGMT activity with a [32P]-labelled oligodeoxynucleotide cleavage assay. A total of 20 subjects were recruited, 12 males and 8 females with a mean age of 68.7±5.8years. There were 14 former and 6 current smokers with a mean smoking exposure of 34.0±18.3packyears. N7-meG (mean 0.75±0.57/106dG, n=65 samples from 14 patients) and MGMT repair (geometric mean 9.57±1.62fmol/μg DNA, n=79 samples from 16 patients) were detected in all samples assayed. MGMT activity increased towards the lung periphery (r=0.28, p=0.023; n=16) with a highly significant association in current (r=0.53, p=0.008; n=6) but not former smokers (r=0.13; p=0.41; n=10). No correlation was seen with N7-meG levels and lung position (r=−0.18; p=0.21; n=14). N7-meG levels were higher in current compared to former smokers reaching significance in two lung positions including peripheral lung (p=0.047). The findings in this study do not support the hypothesis that peripheral tissue is more susceptible to the genotoxic effects of alkylating agents than central lung tissue. In addition exposure to cigarette smoke reduced the level of MGMT in central bronchial tissue possibly through increased alkylating agent exposure.